2013
DOI: 10.1002/hbm.22380
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala excitability to subliminally presented emotional faces distinguishes unipolar and bipolar depression: An fMRI and pattern classification study

Abstract: Distinct amygdala excitability during automatic stages of the processing of emotional faces may reflect differential pathophysiological processes in BD versus MDD depression, potentially representing diagnosis-specific neural markers mostly unaffected by current psychotropic medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 75 publications
6
76
2
Order By: Relevance
“…In our data sensitivity rates outperformed specificity, a finding that is in accordance with the clinical need for sensitive screening instruments to detect psychiatric comorbidity. Accuracy rates were comparable to those of 80% obtained in a pattern analysis study differentiating unipolar from bipolar disorder (Grotegerd et al, 2014) based on amygdalar activation. Accuracies were numerically decreased when accounting for group differences in age, disease onset, and symptom severity (SIGH-A, PAS).…”
Section: Discussionsupporting
confidence: 69%
“…In our data sensitivity rates outperformed specificity, a finding that is in accordance with the clinical need for sensitive screening instruments to detect psychiatric comorbidity. Accuracy rates were comparable to those of 80% obtained in a pattern analysis study differentiating unipolar from bipolar disorder (Grotegerd et al, 2014) based on amygdalar activation. Accuracies were numerically decreased when accounting for group differences in age, disease onset, and symptom severity (SIGH-A, PAS).…”
Section: Discussionsupporting
confidence: 69%
“…For example, several functional neuroimaging studies have shown that amygdala dysfunction is a key feature of BD (Almeida and Phillips, 2012;Blond et al, 2012;Fournier et al, 2013;Grotegerd et al, 2013Grotegerd et al, , 2014Lim et al, 2013), SCZ (Pankow et al, 2013;Rauch et al, 2010), and MDD (Dannlowski et al, 2007;Groenewold et al, 2012;Siegle et al, 2007;Stuhrmann et al, 2011Stuhrmann et al, , 2013Suslow et al, 2010). Also structural imaging studies have demonstrated decreased amygdala volumes in BD (Blumberg et (Hajek et al, 2012a, b;Redlich et al, 2014), although the respective literature is less consistent than that for the amygdala (Blumberg et al, 2003;Hartberg et al, 2011).…”
Section: Discussionmentioning
confidence: 91%
“…Previous neuroimaging studies have already addressed the differentiation of BD and unipolar depression (UD) employing structural (Redlich et al, 2014a;Versace et al, 2010) and functional MRI Benson et al, 2014;Grotegerd et al, 2014). These studies yielded differences in regions that contribute to the dysregulation of emotional and cognitive functions.…”
Section: Introductionmentioning
confidence: 99%